"To make the student exist" - Bilingual subject teachers' narratives about multilingualism in language support classes in Norway - Moraczewska, Agnieszka; Randen, Gunhild Tveit (Bilingual research journal, 2024)
Bilingual subject instruction, designed to facilitate the acquisition of the Norwegian language, is a support class aimed at immigrant students in primary and lower secondary Norwegian schools. This study delves into the beliefs of two Polish-Norwegian bilingual teachers regarding multilingualism in this instructional context and the factors influencing their decisions on incorporating students' prior linguistic knowledge. Utilizing a narrative approach, the analysis of interviews reveals that both teachers perceive multilingualism as valuable for learning support and students' social engagement. Individual variations emerge in how these teachers employ multilingual resources, reflecting a connection between their beliefs, experiences, and reported pedagogical decisions.